Economic, infrastructural and psychological challenges faced by the students of Assam: a study during COVID-19 pandemic - Saikia, Mrinal; Das, Prakash (Society Register, 2024)
A pandemic like the COVID-19 has caught everyone off-guard. The economy is in tatters, and the loopholes in the system are getting exposed. The education sector is no exception, especially in a developing country like India. With millions of students in India, the lockdown will have many unforeseen impacts. Moreover, the parents would be reluctant to send their wards to study even after the pandemic, and the actual effect of a lag in learning would be visible only in the long run. The necessity of e-learning in academia was felt only when the pandemic hit. The lack of ICT infrastructure and the absence of tech-savvy teachers have made studies an absolute roller-coaster ride for students. Apart from this, the already existing disparity between students from different economic strata would very likely broaden. Homebound is another factor affecting the students’ psychology towards study. This paper ventures into the problems faced by the students, especially from economic, infrastructural and psychological factors, ranging from primary to University level. It also attempts to segregate the students based on location and financial condition and understand the specific hindrances they face. Case studies from various locations of Assam provide a cluster of stories that would act as an index in developing the system when time is ‘conducive’.